IoT Driven Vehicle License Plate Extraction Approach - Sheeba Rani Gnanamalar, S; Maheswari, R; Sharmila, B; Gomathy, V (International Journal of Engineering and Technology, 2018)
The objective of the research paper is to capture the design a Vehicle Number Plate Identification System which can be used to identify and read the license number of any vehicle. The basic process involves taking the image of the front/rear of the vehicle which then gets processed and ultimately the number gets displayed on the LCD. This system can be used for a wide variety of installations and establishments such as entry points of schools, colleges, offices and parking spaces. The camera takes an image which is then processed in PC. The result achieved from this is the license number of the vehicle which is then transmitted via the Wi-Fi module and ultimately displayed on the LCD. The hardware especially can be made more rugged and compact so as to handle all the elements of nature and various environments that it can be used in.Â Â
Keywords: Vehicle Number Plate Identification; Optical Character Recognition; Arduino UNO; Image Processing.